Representasi Nilai Moral Dalam Lirik Lagu Folklor Gending Joged Nini (Analisis Semiotika Ferdinand de Saussure Dalam Lirik Lagu Gending Joged Nini) - Suyun Yustika, I Made Dwi; Alit Suryawati, I Gusti Agung; Sugiarica Joni, I Dewa Ayu (E-Jurnal Medium; Vol 2 No 2 (2021): Jurnal Ilmu Komunikasi Vol 2 No 2 Tahun 2021, 2021)
Belief in the power of a mass media to convey something quickly and massive has been growing since ancient times. Song is one of mass media that use to deliver messages and also can use as to representing social phenomenon. Representation is a description or a sign of  meaning in a message. By using song as a media, messages will be conveyed more easily. Like the moral values that contained in Gending Joged Nini. This song describes the fundamental moral values ??that we should have in life. The purpose of this study is to determine the representation of the moral values with the theory of Ferdinand De Saussure. This theory has principle that language is a sign system and devided in two parts, signifier and signified. The results of this study indicate that this song is contained various things that we can do to get prosperity in life.   Keyword : Moral Values, Song, Gending Joged Nini, Ferdinand De Saussure